Towards self-regulated tutoring system: Quantitative study of students' self-regulation strategies during learning episodes - Yusoff M.Z.M.; Zin N.A.M. (2023)
Students' self-regulation ability is an important component for a successful emotionally intelligent tutoring system. Emotion-focused and problem-focused strategies have been recognized as the commonly used strategies by individuals for self-regulation. However, very little work has been done to model self-regulation strategies in affective tutoring system. Thus, this paper presents a qualitative study on students' self-regulation strategies in dealing with potential stressful condition during their learning episodes so that a better framework of suitable adaptive action and reaction by emotionally intelligent tutoring system can be modelled. To get better insight, comparison between genders is also conducted. Results from this study indicate that students used both emotion-focused and problem-focused strategies in dealing with stressful learning episodes. Also, selection of self-regulation strategies is influenced by students' gender. 2011 IEEE.